Contribution of tillage systems and crop succession to soil structuring - Silva, Matheus Flavio da [UNESP]; Fernandes, Mariele Monique Honorato [UNESP]; Fernandes, Carolina [UNESP]; Silva, Amanda Manduca Rosa da [UNESP]; Ferraudo, Antônio Sérgio [UNESP]; Coelho, Anderson Prates [UNESP] (Elsevier, 2021)
The use of conservational systems of soil cultivation has gained importance due to the need for soil preservation and carbon sequestration from the atmosphere. With the objective of evaluating soil structuring, this study determined the physical attributes and organic carbon contents of a clayey Oxisol in an area of 10 years under four different land uses: i.e., afforestation (AF), no-tillage system with grass-grass succession (corn/corn), no-tillage systems with grass-legume succession (corn/Crotalaria juncea L.) and conventional soil tillage system (corn/fallow). The evaluated areas are located in the Cerrado biome of southeastern Brazil. Each area was sampled at 20 points and undisturbed and disturbed samples were collected in the layers of 0.00−0.10 m, 0.10−0.20 m and 0.20−0.30 m. The attributes evaluated were related to soil aggregation and porosity and, due to the structure of dependence of the variables, the data were subjected to multivariate factor analysis. We observed that, after a long period, the no-tillage system promoted soil aggregation and porosity similar to those of the planted forest and superior to those of the conventional tillage system. The type of crop succession in the no-tillage system caused differences in soil structure, and grass-grass succession (corn/corn) promoted better soil structure compared to grass-legume succession (corn/Crotalaria juncea L.). The greater soil porosity generated by the conventional tillage system was limited to the most superficial layer (0.00−0.10 m) and this effect can be considered ephemeral, due to the presence of a large amount of smaller aggregates that, after the operation, can occupy the generated pores.
Keywords: Grass; Legume; Soil aggregation; Soil management; Soil porosity